A lithium ion battery negative electrode material, a lithium ion battery and a method
By using electronic conductor/ion conductor composite materials in lithium-ion batteries and using lithium thermal reaction to prepare heterogeneous interfaces between nano-scale transition metal elements and lithium compounds, the cyclic stability and rate performance problems of lithium-ion batteries under high-rate charging and discharging conditions are solved, and fast charging and discharging and high cycle stability are achieved.
Patent Information
- Application Number
- CN202210880846.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-07-26
AI Technical Summary
Existing lithium-ion batteries have poor cycle stability and low rate performance under high rate charging and discharge conditions, resulting in limited fast charge and discharge capabilities.
An electronic conductor/ion conductor composite material is used as the negative electrode material of lithium-ion battery, and a heterogeneous interface between nano-scale transition metal element and lithium compound is prepared through lithium thermal reaction, and a spin polarization capacitor energy storage mechanism is used to improve rate performance and cyclic stability.
It realizes fast charging and discharging and high cycle stability of lithium-ion batteries while ensuring energy density, improving the rate performance and cycle life of the battery.
Smart Images

Figure CN115458716B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery negative electrode material, a lithium-ion battery and a method. Background Art
[0002] With the continuous development of human society and economy, the demand for fossil resources is increasing, which leads to the depletion of resources, the continuous aggravation of environmental pollution and the increasing global greenhouse effect. The development of new technologies such as exploring new energy and reducing carbon dioxide emissions has become an extremely urgent need for mankind. Chemical energy storage devices are a very important part of the energy system, among which metal ion batteries including lithium ion batteries, sodium ion batteries, potassium ion batteries, etc. have attracted much attention.
[0003] Lithium-ion batteries (LIBs) have been widely used in electric vehicles and various portable electronic energy storage devices. They are one of the most effective means to solve environmental pollution and energy crisis problems and have broad development prospects. However, due to the slow reaction kinetics and low equilibrium potential of carbon materials, lithium metal deposition will form at the negative electrode of lithium-ion batteries under high-rate charge and discharge conditions. This will greatly limit the rapid charge and discharge capabilities and cycle stability of lithium-ion batteries.
[0004] At present, it is still very challenging to achieve fast charging and discharging of lithium-ion batteries while ensuring energy density. A new type of lithium-ion battery anode material with high rate performance and high cycle stability is urgently needed. Summary of the invention
[0005] The embodiments of the present application provide a lithium ion battery negative electrode material, a lithium ion battery and a method, which are useful for solving the problems of poor cycle stability and / or low rate performance of lithium ion batteries in the prior art.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing an electronic conductor / ion conductor composite material, comprising the following steps:
[0007] Placing lithium metal in a tantalum crucible in a protective gas atmosphere, and heating the crucible on a heating table with a heating function until the lithium metal is in a molten state;
[0008] Will Me m X n Add it into the molten lithium metal, and keep mechanical stirring until the reaction is complete and the product is a powdery solid;
[0009] Wherein, Me is one of transition metal elements such as Fe, Co, Ni, etc., and X is one of O, F, S, and N; the average valence of Me is α, the average valence of X is β, and the relationship between m and n satisfies |m*α|=|n*β|;
[0010] The heating stage is heated up, and the powdered solid is solid-phase calcined while being mechanically stirred to obtain an electronic conductor / ion conductor composite material.
[0011] In a possible implementation, the lithium metal element is a lithium sheet or lithium powder; the lithium metal element and Me m X n The molar ratio of the raw materials was maintained at Li element:Me element=|m*α|:1.
[0012] In a possible implementation, the temperature of the crucible when the lithium metal is heated to a molten state is 180° C.-190° C.; the material of the crucible is 99.95% tantalum, and the material of the stirring rod used for mechanical stirring is 310S stainless steel.
[0013] In one possible implementation, the slowly m X n Add to the molten lithium metal, and keep mechanical stirring until the reaction is complete, including:
[0014] Slowly, Me m X n Add to the molten lithium metal, while maintaining mechanical stirring, m X n After the molten lithium metal is completely added, mechanical stirring is continued for 20 minutes to ensure complete reaction.
[0015] In a possible implementation, the step of heating the heating stage to solid-phase calcinate the powdered solid includes:
[0016] The heating stage is heated to 200° C.-240° C., and the powdered solid is solid-phase calcined for a calcination time of 1.5 h-3 h.
[0017] In a possible implementation, the electron conductor / ion conductor negative electrode material has the general formula of Me / Li a X V b , b*|V|=a; wherein Me is one of transition metal elements such as Fe, Co, Ni, etc.; X is one of O, F, S, N, and V is the average valence of X.
[0018] In a possible implementation, the protective gas atmosphere is an argon atmosphere.
[0019] In a second aspect, an embodiment of the present application provides a negative electrode material for a lithium-ion battery, including a copper foil and a coating layer, wherein the coating layer is a mixed slurry of an electronic conductor / ion conductor composite material, a conductive agent and polyvinylidene fluoride prepared by the method described in any one of the first aspects.
[0020] In a third aspect, the present application provides a method for preparing a negative electrode material for a lithium-ion battery, comprising:
[0021] Prepare an electron conductor / ion conductor composite material by the method described in any one of the first aspects;
[0022] The electronic conductor / ion conductor composite material, the conductive agent and polyvinylidene fluoride are uniformly mixed in a glove box filled with argon atmosphere to obtain a mixed slurry;
[0023] The mixed slurry is coated on a copper foil and dried on a heating table in a glove box filled with an argon atmosphere to obtain a negative electrode material for a lithium ion battery.
[0024] In a fourth aspect, an embodiment of the present application provides a lithium-ion battery, comprising the lithium-ion battery negative electrode material described in the second aspect.
[0025] The electronic conductor / ion conductor composite material provided in the embodiment of the present application has the following advantages when applied to negative electrode materials of lithium-ion batteries:
[0026] 1) Electronic conductor / ion conductor composite materials are based on the spin-polarized capacitor energy storage mechanism and have ultra-high rate performance, which can achieve rapid charging and discharging while ensuring a certain energy density.
[0027] 2) The electronic conductor / ion conductor composite material utilizes the heterojunction interface formed by nanoscale transition metal elements and lithium compounds for interfacial energy storage. The interface has high stability, which leads to high cycle stability of the electronic conductor / ion conductor composite material.
[0028] The method for preparing the electronic conductor / ion conductor composite material provided in the embodiment of the present application has the following characteristics:
[0029] The embodiment of the present application adopts lithium thermal reaction for preparation, which is different from the previous negative electrode material preparation method and is a new material preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 A schematic diagram of the nanostructure and spin-polarized capacitor energy storage mechanism of an electronic conductor / ion conductor composite material provided in an embodiment of the present application;
[0032] Figure 2 A schematic diagram of a process for preparing a novel high-performance electron conductor / ion conductor negative electrode material provided in an embodiment of the present application;
[0033] Figure 3 X-ray diffraction (XRD) patterns of electronic conductor / ion conductor composite materials with different elemental compositions provided in the embodiments of the present application;
[0034] Figure 4 A scanning electron microscope image of an electronic conductor / ion conductor composite material provided in Example 1 of the present application;
[0035] Figure 5 The electronic conductor / ion conductor composite material provided in Example 2 of the present application is 10A g -1 Cycle performance diagram below;
[0036] Figure 6 The electronic conductor / ion conductor composite material provided in Example 3 of the present application is -1 Cycle performance diagram below;
[0037] Figure 7 A rate performance diagram of the electronic conductor / ion conductor negative electrode material provided in Example 4 of the present application at 100C to 500C;
[0038] Figure 8 A schematic flow chart of a method for preparing a negative electrode material for a lithium-ion battery provided in an embodiment of the present application. DETAILED DESCRIPTION
[0039] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.
[0040] The nano-sizing of electrode materials will lead to a significant increase in the specific surface area of the material and the interface formed. Using nano-scale material internal interfaces for energy storage is a new energy storage solution with great development potential. Spin polarized capacitors, as a new energy storage mechanism occurring at the interface, have great prospects for development and utilization. The embodiment of the present application adopts a new lithium thermal reaction scheme to prepare an electronic conductor / ion conductor composite material, and by constructing a heterogeneous interface between nano-scale transition metal single substance particles and lithium compounds, the spin polarized capacitor energy storage is used to achieve ultra-high rate performance and ultra-long cycle stability of the material.
[0041] Figure 1 A schematic diagram of the nanostructure and spin polarized capacitor energy storage mechanism of an electronic conductor / ion conductor composite material provided in the embodiment of the present application. Figure 1 As shown in the figure, nanoscale transition metal particles (electronic conductors) are attached to the surface and interior of lithium compounds (ionic conductors), forming a heterogeneous interface between the two; at the Fermi level of the transition metal particles, the majority state density with spin up is smaller than the minority state density with spin down, and a large number of spin-polarized electrons are stored in the spin-split energy band of the transition metal nanoparticles, while lithium ions accumulate at the boundary or surface of the other phase. This is a new energy storage mechanism that is similar to physical adsorption, and the speed of storing / releasing charges is extremely fast.
[0042] The electronic conductor / ion conductor composite material provided in the embodiment of the present application has the following advantages when applied to negative electrode materials of lithium-ion batteries:
[0043] 1) The electronic conductor / ion conductor composite material is based on the spin polarized capacitance energy storage mechanism. The basic principle is a new energy storage mechanism that is similar to physical adsorption. It has ultra-high rate performance and can achieve ultra-fast charging and discharging while ensuring a certain energy density.
[0044] 2) The electronic conductor / ion conductor composite material utilizes the heterojunction interface formed by nanoscale transition metal elements and lithium compounds for interfacial energy storage. This interface has high stability and the material structure is not easily destroyed during the cycle, resulting in the electronic conductor / ion conductor composite material having extremely high cycle stability.
[0045] Figure 2 A schematic diagram of a preparation method of an electronic conductor / ion conductor composite material provided in an embodiment of the present application is shown in FIG. Figure 2 As shown, the method mainly includes the following steps.
[0046] Step S201: placing lithium metal in a tantalum crucible in a protective gas atmosphere, and heating the crucible on a heating table with a heating function until the lithium metal is in a molten state.
[0047] Specifically, in a glove box filled with protective gas, a certain amount of metallic lithium is weighed, placed in a tantalum crucible, and heated on a heating plate until the metallic lithium reaches its melting point, thereby turning it into a molten state.
[0048] In an optional embodiment, the metallic lithium is lithium powder and / or lithium flakes.
[0049] In an optional embodiment, the heating on the heating plate until the melting point of the metal lithium is reached to make it molten, the temperature reached by heating is 180°C-190°C. If the temperature reached by heating is too low, the metal lithium cannot reach the melting point and cannot melt; if the temperature reached by heating is too high, it may greatly increase the intensity of the subsequent reaction, which may easily cause danger and cause impurities in the final product.
[0050] Step S202: Me m X n Add it into the molten lithium metal, keep mechanical stirring until the reaction is complete and the product is a powdery solid.
[0051] Specifically, Me m X n Use a stainless steel spoon to slowly add the molten lithium metal in batches. The amount added each time should not exceed 20 mg. m X n Too much may lead to more severe reaction, which may cause danger and affect the composition of the final product. m X n Afterwards, use a 310S stainless steel stirring rod to stir the mixture evenly before adding the next portion of Me m X n . In Me m X n After the molten metal lithium is completely added, the molten reaction temperature should be maintained and stirring should be continued for 20 minutes to ensure complete reaction.
[0052] In an optional embodiment, for the Me m X n , Me is one of the transition metal elements such as Fe, Co, Ni, etc., X is one of O, F, S, N; the average valence of Me is α, the average valence of X is β, and the relationship between m and n satisfies |m*α|=|n*β|.
[0053] In an optional embodiment, the lithium metal and Me m X n The raw material ratio should be Li element:Me element = |m*α|:1. If the lithium metal element is too much, Me m X nIf the amount of lithium metal is too small, the final product will contain excessive metallic lithium impurities, affecting the material properties; on the contrary, if the amount of lithium metal is too small, Me m X n Too much will result in the final product containing Me that has not been completely reacted. m X n Impurities.
[0054] Step S203: raising the temperature of the heating platform and subjecting the powdered solid to solid-phase calcination while maintaining mechanical stirring to obtain an electronic conductor / ion conductor composite material.
[0055] Specifically, the heating table is heated to a specific reaction temperature, and the powdered solid is solid-phase calcined. The calcination time is usually 1.5h-3h, during which the mixture must be mechanically stirred using a 310S stainless steel stirring rod. If the calcination time is too short, the reaction will not be completely carried out, and the product may contain a small amount of impurities; if the calcination time is too long, it is unnecessary.
[0056] Figure 3 The X-ray diffraction (XRD) patterns of the electronic conductor / ion conductor composite materials with different elemental compositions provided in the embodiments of the present application, wherein JCPDS:06-0696, JCPDS:12-0254, JCPDS:30-0759, JCPDS:04-0850, and JCPDS:40-0857 are all X-ray diffraction standard cards launched by the Joint Committee on Powder Diffraction Standards. Figure 3 As shown, the positions of the diffraction peaks of the electronic conductor / ion conductor composite material prepared in the embodiment of the present application correspond one to one with the standard card, indicating that the sample prepared in the embodiment of the present application is a pure phase electronic conductor / ion conductor composite.
[0057] For ease of understanding, the embodiments of the present application provide a variety of specific implementations of the preparation methods of high-performance electronic conductor / ion conductor negative electrode materials. It should be pointed out that the following are only a few specific implementations, and they should not be used as limitations on the protection scope of the present application. Those skilled in the art can make appropriate adjustments according to actual needs, and they should all fall within the protection scope of the present application.
[0058] Example 1
[0059] In a glove box filled with argon atmosphere, weigh 0.240g of single lithium sheet and place it in a tantalum crucible, and place the crucible on a heating table and heat it to 185°C. After the lithium sheet is completely melted, weigh 1.520g of ferrous sulfide and add it to the molten metal lithium in small amounts with a spoon, and use a stainless steel stirring rod to maintain mechanical stirring during the process. After mixing evenly, continue to stir at 185°C for 20 minutes. Then raise the temperature of the heating table to 220°C and continue stirring for 2 hours. After the reaction is completed, cool naturally to obtain the final product in the form of black powder, i.e., Fe / Li2S composite material.
[0060] Figure 4 This is a scanning electron microscope image of an electronic conductor / ion conductor composite material provided in Example 1 of the present application. Figure 4 As shown, the morphology of the sample is nanospheres.
[0061] Example 2
[0062] In a glove box filled with argon atmosphere, weigh 0.240g of single lithium sheet and place it in a tantalum crucible, and place the crucible on a heating table and heat it to 185℃. After the lithium sheet is completely melted, weigh 1.000g of ferroferric oxide and add it to the molten metal lithium in small amounts with a spoon, and use a stainless steel stirring rod to maintain mechanical stirring during the process. After mixing evenly, continue to stir at 185℃ for 20min. Then raise the temperature of the heating table to 200℃ and continue stirring for 2h. After the reaction is completed, cool it naturally to obtain the final product in black powder form, that is, Fe / Li2O composite material.
[0063] Figure 5 The electronic conductor / ion conductor composite material provided in Example 2 of the present application is -1 The cycle performance diagram below is Figure 5 It can be seen that the material can be used at 10A g -1 At a high current density of 250 mAh g -1 The capacity of the battery can be stably charged and discharged for 30,000 cycles, indicating that the material has ultra-high cycle stability.
[0064] Example 3
[0065] In a glove box filled with argon atmosphere, weigh 0.240g of single lithium sheet and place it in a tantalum crucible, and place the crucible on a heating table and heat it to 185°C. After the lithium sheet is completely melted, weigh 1.622g of ferrous fluoride and add it to the molten metal lithium in small amounts with a spoon, and use a stainless steel stirring rod to maintain mechanical stirring during the process. After mixing evenly, continue to stir at 185°C for 20 minutes. Then raise the temperature of the heating table to 240°C and continue stirring for 2 hours. After the reaction is completed, cool naturally to obtain the final product in black powder form, that is, Fe / LiF composite material.
[0066] Figure 6 The electronic conductor / ion conductor composite material provided in Example 3 of the present application is -1 The cycle performance diagram below is Figure 6 It can be seen that the material can be used at 10A g -1 At a high current density of 220 mAh g -1 The capacity of the material was stably charged and discharged for 30,000 cycles, indicating that the material has ultra-high cycle stability.
[0067] In a glove box filled with argon atmosphere, weigh 0.240g of single lithium sheet and place it in a tantalum crucible, and place the crucible on a heating table and heat it to 185°C. After the lithium sheet is completely melted, weigh 0.500g of ferroferric oxide and 0.460g of ferric oxide, and add them to the molten metal lithium in small amounts with a spoon, and use a stainless steel stirring rod to maintain mechanical stirring during the period. After mixing evenly, continue to stir at 185°C for 20 minutes. Then raise the temperature of the heating table to 200°C and continue stirring for 2 hours. After the reaction is completed, cool naturally to obtain the final product in the form of black powder, that is, Fe / Li2O composite material.
[0068] Figure 7 The rate performance diagram of the electronic conductor / ion conductor composite material provided in Example 4 of the present application at 100C to 500C is shown in FIG. Figure 7 It can be seen that the first charge capacity of the material at the rates of 100C, 150C, 200C, 250C, 300C, 350C, 400C, 450C, and 500C is 330.5mAh g -1 , 283.3mAh g -1 , 238.8mAh g -1 , 208.4mAh g -1 、191.7mAh g -1 、175.0mAh g -1 、166.7mAh g -1 、150.0mAh g -1 , 138.9mAh g -1 , indicating that the material has ultra-high rate performance.
[0069] Example 5
[0070] In a glove box filled with argon atmosphere, weigh 0.240g of single lithium powder and place it in a tantalum crucible, and place the crucible on a heating table and heat it to 185°C. After the lithium sheet is completely melted, weigh 1.449g of iron nitride and add it to the molten metal lithium in small amounts with a spoon, and use a stainless steel stirring rod to maintain mechanical stirring during the process. After mixing evenly, continue to stir at 185°C for 20 minutes. Then raise the temperature of the heating table to 200°C and continue stirring for 2 hours. After the reaction is completed, cool it naturally to obtain the final product in black powder form, that is, Fe / Li3N composite material.
[0071] Example 6
[0072] In a glove box filled with argon atmosphere, weigh 0.240g of single lithium sheet and place it in a tantalum crucible, and place the crucible on a heating table and heat it to 185°C. After the lithium sheet is completely melted, weigh 1.000g of ferroferric oxide and add it to the molten metal lithium in small amounts with a spoon, and use a stainless steel stirring rod to maintain mechanical stirring during the process. After mixing evenly, continue to stir at 185°C for 20 minutes. Then raise the temperature of the heating table to 210°C and continue stirring for 2 hours. After the reaction is completed, cool naturally to obtain the final product in black powder form, that is, Fe / Li2O composite material.
[0073] Example 7
[0074] In a glove box filled with argon atmosphere, weigh 0.240g of single lithium sheet and place it in a tantalum crucible, and place the crucible on a heating table and heat it to 190°C. After the lithium sheet is completely melted, weigh 1.292g of nickel oxide and add it to the molten metal lithium in small amounts with a spoon, and use a stainless steel stirring rod to maintain mechanical stirring during the process. After mixing evenly, continue to stir at 190°C for 20 minutes. Then raise the temperature of the heating table to 210°C and continue stirring for 2 hours. After the reaction is completed, cool naturally to obtain the final product in black powder form, i.e., Ni / Li2O composite material.
[0075] Example 8
[0076] In a glove box filled with argon atmosphere, weigh 0.240g of single lithium sheet and place it in a tantalum crucible, and place the crucible on a heating table and heat it to 185°C. After the lithium sheet is completely melted, weigh 1.676g of cobalt fluoride and add it to the molten metal lithium in small amounts with a spoon, and use a stainless steel stirring rod to maintain mechanical stirring during the process. After mixing evenly, continue to stir at 185°C for 20 minutes. Then raise the temperature of the heating table to 240°C and continue stirring the reaction for 1.5 hours. After the reaction is completed, cool it naturally to obtain the final product in the form of black powder, i.e., Co / LiF composite material.
[0077] Based on the above-mentioned electronic conductor / ion conductor composite material, the embodiment of the present application also provides a lithium-ion battery negative electrode material and a preparation method thereof.
[0078] Figure 8 A schematic diagram of a method for preparing a negative electrode material for a lithium-ion battery provided in an embodiment of the present application is shown in FIG. Figure 8 As shown, it mainly includes the following steps: Step S801: uniformly mix the electronic conductor / ion conductor composite material, the conductive agent and polyvinylidene fluoride to obtain a mixed slurry.
[0079] The electronic conductor / ion conductor composite material is Figure 2 The electronic conductor / ion conductor composite material prepared by the method, the conductive agent can improve the electronic conductivity of the material, and the polyvinylidene fluoride is used to improve the adhesion of the material. In a specific implementation, the mixture can be uniformly mixed in a glove box filled with argon atmosphere. The conductive agent can be a Super P conductive agent.
[0080] Step S802: coating the mixed slurry on a copper foil, and drying it on a heating table in a glove box filled with argon atmosphere to obtain a negative electrode material for a lithium-ion battery.
[0081] In the specific implementation, the material obtained in the embodiment, the conductive agent and the binder polyvinylidene fluoride are weighed and mixed in an agate mortar at a mass ratio of 70:20:10, and ground. After grinding evenly, N-methylpyrrolidone is used as a solvent, fully stirred into a paste, and then evenly applied to the copper foil with an applicator, fully dried at 60°C for 12 hours, and cut into a circular electrode sheet with a diameter of 1 cm; or after grinding evenly, N-methylpyrrolidone is used as a solvent, fully stirred into a paste, and evenly applied to a circular copper foil with a diameter of 1 cm with a pipette gun, and fully dried at 60°C for 12 hours.
[0082] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0083] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
[0084] In this specification, the same or similar parts between the various embodiments can be referred to each other. In particular, for the terminal embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the description in the method embodiment.
[0085] The above-described embodiments of the present application do not constitute a limitation on the protection scope of the present application.
Claims
1. A method for preparing an electronic conductor / ion conductor composite material, characterized in that: The following steps are involved: Placing a lithium metal element in a tantalum crucible in a protective gas atmosphere, and heating the crucible on a heating table with a heating function until the lithium metal element is in a molten state, wherein the temperature at which the crucible is heated to the molten state of the lithium metal element is 180° C.-190° C.; Slowly, Me m X n Use a stainless steel spoon to slowly add the molten lithium metal in batches, and keep mechanical stirring until the reaction is complete and the product is a powdery solid. m X n The raw material mass ratio should be maintained at Li element:Me element = |m*α|:1; Wherein, Me is one of the transition metal elements Fe, Co, and Ni, and X is one of O, F, S, and N; the average valence of Me is α, the average valence of X is β, and the relationship between m and n satisfies |m*α|=|n*β|; The heating stage is heated to a specific reaction temperature, and the powdered solid is solid-phase calcined for 1.5 h to 3 h, during which mechanical stirring is maintained to obtain an electronic conductor / ion conductor composite material. The electronic conductor / ion conductor composite material has a general formula of Me / Li a X V b , b*|V|=a.
2. The method according to claim 1, characterized in that: The lithium metal element is lithium flakes or lithium powder.
3. The method according to claim 1, characterized in that The material of the tantalum crucible is 99.95% tantalum, and the material of the stirring rod used for the mechanical stirring is 310S stainless steel.
4. The method according to claim 1, characterized in that The slowness will m X n Use a stainless steel spoon to slowly add the mixture in batches to the molten lithium metal, while maintaining mechanical stirring until the reaction is complete, including: Slowly, Me m X n Use a stainless steel spoon to slowly add the mixture in batches into the molten lithium metal, while maintaining mechanical stirring. m X n After the molten lithium metal is completely added, mechanical stirring is continued for 20 minutes to ensure complete reaction.
5. The method according to claim 1, characterized in that The step of heating the heating stage to a specific reaction temperature and subjecting the powdered solid to solid phase calcination comprises: The heating stage is heated to 200° C.-240° C. to perform solid phase calcination on the powdered solid.
6. The method according to claim 5, characterized in that The protective gas atmosphere is an argon atmosphere.
7. A negative electrode material for a lithium ion battery, characterized in that: The invention comprises a copper foil and a coating layer, wherein the coating layer is a mixed slurry of an electronic conductor / ion conductor composite material prepared by the method described in any one of claims 1 to 6, a conductive agent and polyvinylidene fluoride.
8. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: include: The electronic conductor / ion conductor composite material is prepared by the method according to any one of claims 1 to 6; The electronic conductor / ion conductor composite material, the conductive agent and polyvinylidene fluoride are uniformly mixed in a glove box filled with argon atmosphere to obtain a mixed slurry; The mixed slurry is coated on a copper foil and dried on a heating table in a glove box filled with an argon atmosphere to obtain a negative electrode material for a lithium ion battery.
9. A lithium ion battery, characterized in that: Including the lithium-ion battery negative electrode material as described in claim 7.
Citation Information
Patent Citations
Process for preparing electroactive insertion compounds and electrode materials obtained therefrom
US20060127767A1
Lithium-Rich Anode Material, Lithium Battery Anode, and Lithium Battery
US20140127581A1